Katja Ritari & Alexandra Bergholm (eds.): Understanding Celtic Religion: Revisiting the Pagan Past - Philip Freeman (Entangled Religions - Interdisciplinary Journal for the Study of Religious Contact and Transfer, 2017)
This contribution offers a review of: